2018
DOI: 10.1111/bju.14139
|View full text |Cite
|
Sign up to set email alerts
|

Robot‐assisted partial nephrectomy for large renal masses: a multi‐institutional series

Abstract: For T2a tumours RAPN is a feasible treatment option in a select patient population when performed by experienced surgeons in institutions equipped to manage postoperative complications. Although RAPN was associated with greater blood loss and longer operating and ischaemia time in T2a tumours, it was not associated with greater complication or positive surgical margin rates compared with T1 tumours. Renal function preservation rates were equivalent for up to 24 months postoperatively; however, 12-month recurre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
17
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 35 publications
1
17
1
Order By: Relevance
“…20,21 A recent study of RPN reported low positive surgical margin rates, with 3.3% for cT1b renal tumors and 4.5% for cT2a renal tumors. 13 Our results with patients with ‡4 cm renal tumors also demonstrated lower positive margin rates with 1.7% for TRPN and 0% for RRPN. These results could be attributable to a single skillful surgeon performing surgeries in our study.…”
Section: Discussionsupporting
confidence: 55%
See 2 more Smart Citations
“…20,21 A recent study of RPN reported low positive surgical margin rates, with 3.3% for cT1b renal tumors and 4.5% for cT2a renal tumors. 13 Our results with patients with ‡4 cm renal tumors also demonstrated lower positive margin rates with 1.7% for TRPN and 0% for RRPN. These results could be attributable to a single skillful surgeon performing surgeries in our study.…”
Section: Discussionsupporting
confidence: 55%
“…Retrospective studies reported patients with cT2a tumors demonstrated less differences in eGFR at 12 months than patients with with cT1 tumors after open, LPN and RPN. 13,29 Before our study, however, no studies have compared reduction in eGFR after one postoperative year between TRPN and RRPN in patients with ‡4 cm renal tumors. In our study, change in eGFR at 1 year postoperation was significantly more decreased at 1 year after RRPN than after TRPN for all patients ( p = 0.006) and patients with ‡4 cm renal tumors ( p = 0.008).In patients with ‡4 cm renal tumors, mean decrease in eGFR at 1 year postoperation was more than 10% for RRPN.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, these were based on renal masses in general (and actually mostly small ones of <4 cm). For the specific group of renal tumours of >4 cm, previous studies have reported the feasibility and safety of LPN [7][8][9] and RAPN [10][11][12][13][14]. The advantages of RAPN over LPN for renal tumours of >4 cm still needs to be validated and specified.…”
Section: Discussionmentioning
confidence: 99%
“…However, a laparoscopic approach may have more pronounced technical challenges than an open approach. RAPN can be considered as an evolution of LPN, with a number of published series proving its feasibility and safety for managing renal tumours of >4 cm [10][11][12][13][14].…”
Section: Introductionmentioning
confidence: 99%